Exploring Fifth Graders’ Learning Obstacles in Multiplication and Division of Fractions - Puji Lestari; Unik Ambarwati; Yoppy Wahyu Purnomo; Kinanti Pangestu (STAI Hubbulwathan Duri, 2025)
Fractions serve as a critical foundation in mathematics education, preparing students for more advanced topics such as algebra and probability. Despite their importance, fractions are often difficult for elementary school students to grasp due to their abstract nature, especially when not taught within meaningful contexts. This study investigates the learning obstacles faced by fifth-grade students in understanding the multiplication and division of fractions. Utilizing a qualitative case study approach, data were collected through tests, interviews, classroom observations, and documentation at Lempuyangwangi Elementary School in Yogyakarta. The analysis revealed three primary categories of learning obstacles: (1) Ontogenic obstacles, including students’ inability to simplify fractions correctly, frequent computational errors, and low motivation in learning mathematics; (2) Didactical obstacles, such as difficulties in interpreting word problems and applying appropriate procedures; and (3) Epistemological obstacles, particularly in understanding and applying the inverse concept required for dividing fractions. These findings highlight the need for more contextually relevant and cognitively aligned instructional strategies. Addressing these obstacles can support the development of more effective teaching approaches to enhance students’ conceptual understanding of fraction operations.